Fundamentals of engineering thermodynamics - Moran, Michael J.; Shapiro, Howard N. ([S.l.] : Wiley, 2007)
Now in a Sixth Edition, Fundamentals of Engineering Thermodynamics maintains its engaging, readable style while presenting a broader range of applications that motivate student understanding of core thermodynamics concepts. This leading text uses many relevant engineering-based situations to help students model and solve problems.